SPECTRUM OF RELAXATION PROCESSES OF POLYBROMOPRENE - Babayan, Yu. S.; Ovanesov, G. T.; Grigoryan, Z. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
Relaxation processes are typical for polybromoprene, which are connected with the dipol-segmental mobility (α-processes), dipol-group (β-processes) and by chemical structure (γ-processes). In addition to these basic relaxation processes in certain conditions, other processes, which are connected with the overmolecular structure of the polymer, show themselves as well. These relaxation processes reflect the cooperativeness of thermal molecular mobility of separate types of macromolecular parts of intercrystalline fields. They are also connected with the mobility of kinetic elements of macromolecules of the amorphous polymer, which save information about the crystal condition.